Problemy w leczeniu chirurgicznym pierwotnie przetrwałego ciała szklistego u dzieci - Kanigowska, Krystyna; Grałek, Mirosława; Chipczyńska, Barbara; Hautz, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: To evaluate the surgical techniques that allows safe, effective removal of lens and retrolenticular fibrotic membranes in eyes with PHPV in children. Material and methods: A total of 31 children (18 boys and 13 girls) with PHPV and cataract in one eye were divided into 2 groups, according to treatment modality. High frequency ultrasonography were used to identify anatomic correlates in the eyes – before operation. Limbal cataract extraction combined with vitrectomy and removal of embryonic remnants was carried out in 17 eyes, and a posterior pars plana approach in 14 eyes. Results: In group with anterior approach, the most serious complication was corneal decompensation, in the next group – retinal detachement. Conclusions: The anterior and the posterior surgical technique to remove cataract and tenacious retrolenticular membranes was effective but associated with high risk of intraoperative and postoperative complications. Although the surgical intervention is necessary to prevent progressive pathologic changes and to obtain the best possible visual results in some cases.